Breastfeeding duration: does parity influence? A longitudinal investigation: the pro-saude study - REBECA N.M. DA SILVA; EDUARDO FAERSTEIN (Anais da Academia Brasileira de Ciências)
Abstract Breastfeeding experiences differ between primiparous and multiparous women. This study aims to investigate how parity influences breastfeeding duration among Brazilian women and to examine the relationship between the number of siblings and the duration of breastfeeding for each child. Data from the Pró-Saúde Study (1999-2012) were used to analyze breastfeeding duration. Differences between parity groups were tested using the chi-square test, while Kruskal-Wallis test and analysis of variance assessed variations in breastfeeding duration, with comparisons visualized using Kaplan-Meier plots. Characteristics such as maternal age and mode of delivery are relevant, especially among primiparous mothers, while maternal education and household income have a positive impact on breastfeeding duration. The use of the Cox model to analyze breastfeeding duration highlights the need for further investigation into the factors influencing this practice, especially considering the decrease in breastfeeding duration among children born in the 1990s and 2000s. These results point to the complex interaction of social, economic, and behavioral factors that should be considered in public policies aimed at maternal and child health.